Seasonal changes in bird communities on poultry farms and house sparrow—wild bird contacts revealed by camera trapping - Sánchez-Cano, Alberto; Camacho, Maria-Cruz; Ramiro, Yolanda; Cardona-Cabrera, Teresa; Höfle, Ursula (Frontiers in Veterinary Science, 2024)
Wild birds are considered reservoirs of poultry pathogens although transmission routes have not been conclusively established. Here we use camera trapping to study wild bird communities on commercial layer and red-legged partridge farms over a one-year timeframe. We also analyze direct and indirect interactions of other bird species with the house sparrow (Passer domesticus), a potential bridge host. We conducted camera trapping events between January 2018 and October 2019, in two caged layer farms, one free-range layer farm, and two red-legged partridge farms in South-Central Spain. We observed wild bird visits on all types of farms, with the significantly highest occurrence on red-legged partridge farms where food and water are more easily accessible, followed by commercial caged layer farms, and free-range chicken farms. The house sparrow (Passer domesticus) followed by spotless starlings (Sturnus unicolor) was the most encountered species on all farms, with the highest frequency in caged layer farms.On partridge farms, the house sparrow accounted for 58% of the wild bird detections, while on the free-range chicken farm, it made up 11% of the detections. Notably, the breeding season, when food and water are scarce in Mediterranean climates, saw the highest number of wild bird visits to the farms. Our findings confirm that the house sparrow, is in direct and indirect contact with layers and red-legged partridges and other wild birds independent of the type of farm. Contacts between house sparrows and other bird species were most frequent during the breeding season followed by the spring migration period. The species most frequently involved in interactions with the house sparrow belonged to the order Passeriformes. The study provides a comparative description of the composition and seasonal variations of bird communities in different types of layer/ poultry farms ins Southern Spain i. e. a Mediterranean climate. It confirms the effectiveness of biosecurity measures that restrict access to feed and water.Additionally, it underscores the importance of synanthropic species, particularly the house sparrow, as potential bridge vector of avian pathogens.